Enhanced electrochemical performance of modified thin carbon electrodes for all-vanadium redox flow batteries. Issue 6 (28th August 2020) - Sodiq, Ahmed; Fasmin, Fathima; Mohapatra, Lagnamayee; Mariyam, Sabah; Arunachalam, Muthumeenal; Hamoudi, Hicham; Zaffou, Rachid; Merzougui, Belabbes
Abstract : The significance of this work lies in the promotion of thin carbon paper as well as its treatment (such as the one presented in this work) as electrodes for flow batteries, in particular VRFB reactions. Abstract : We report the unique electrochemical properties of nitrogen-containing carbon nanostructures (N-CP) grown on commercial carbon paper (CP), used as electrocatalysts in all-vanadium redox flow batteries (VRFBs). The focus is on the anode, where mitigation of the hydrogen evolution reaction and loss in redox kinetics due to cycling is considered as a challenge. The growth of bamboo-like carbon nanostructures is achieved through a catalytic chemical vapor deposition (CVD) process with a very small geometric loading of Fe (from FeCl3 ) as the catalyst. Anhydrous acetonitrile, used as a nitrogen/carbon precursor, is fed to the electrode sample at 900 °C for 3 hours in a stream of H2 –Ar (carrier gas). The three-electrode-cell study shows enhanced kinetics and durability of the electrode for V 3+ /V 2+ redox reactions; N-CP shows a significant suppression of the peak potential separation (Δ E ∼ 80 mV), indicating faster kinetics compared to conventional CP (Δ E ∼ 160 mV). In addition, the subscale cell performance shows good durability (about 5% and 15% loss in energy efficiency in N-CP and CP, respectively) after 50 charge–discharge cycles. The improved durability of the N-CP electrode is attributed to the presence of nitrogen–carbon nanostructures, increased active area, and improved sp 2 carbon content. Such findings can contribute to the development of large scale high performance VRFB systems.